Neuro-fuzzy profile clustering in image enhancement - Ngernplubpla, Jaturon; Chitsobhuk, Orachat (My University, 2019)
This paper proposes a technique for clustering features into profile groups to obtain optimum enhancement weights for reconstructing high resolution images. Neuro-fuzzy model, which combines the fuzzy reasoning behavior with the adaptive learning capability and connectionist structure of neural networks, is adopted to analyze and learn with gradient data and statistics and to generate gradient profile priors. In enhancement process, the optimum weights are appropriately chosen according to the gradient profile priors. From the experimental results, the proposed algorithm demonstrates quantitative performance improvement in classifying data and perceptual improvement in recovery of the high-resolution image.
Keywords: Gradient prior; Gradient profile generation; Image Enhancement; Neuro-fuzzy clustering